200% wolf [videorecording (DVD)] - Edquist, Fin; Weinbrecht, Adrian; Greig, Ash Gibson (Viva Pictures, 2024)
Heroic poodle Freddy Lupin has everything it takes to lead the werewolf pack. Except respect. When a wayward wish to the moon transforms him into a wolf, he and his friends, enlist a legendary villain to save the cosmos and the pack.